Geopolitik Energi dan Keamanan Global Perebutan Sumber Daya dalam Perspektif Strategis: (Studi Kasus Venezuela) - Laurensius Ryan Prasetia Tungary S (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
This research analyzes the interconnection between energy geopolitics and global security through the case study of Venezuela, the country with the world's largest proven oil reserves. The background highlights that energy has become a strategic commodity driving geopolitical tensions in the international system. The objective is to answer three fundamental questions: why energy is critically needed, how the distribution of the world's oil reserves creates strategic inequality, and how the Venezuela case illustrates resource grabbing mechanisms. The method used is qualitative with a single case study approach, employing neorealism and dependency theory as analytical frameworks, with data sourced from official reports of international organizations (OPEC, IEA, IMF, EIA), news media, and academic literature. The findings reveal that the United States' escalating pressure on Venezuela from economic sanctions, maritime blockades, to military threats reflects a systematic pattern of resource imperialism disguised as counter-narcotics efforts. The impact on Venezuela includes GDP contraction of 4 percent, hyperinflation exceeding 530 percent, and 8 million people displaced. The implications underscore that the current global energy order remains dominated by zero-sum logic, requiring reform of international energy governance to be more just and sustainable.